Kemandirian Belajar Siswa dalam Pembelajaran Daring Fisika Berbantuan Modul Berbasis Masalah ditinjau dari Hasil Belajar Kognitif Siswa - Roosilawati, Erwin; Hartono, Hartono (UPEJ Unnes Physics Education Journal, 2021)
The purpose of this research is to analyze student learning independence in terms of student cognitive learning outcomes in online learning physics assisted by problem-based modules. This type of this research is a pre-experimental design research with one group pretest posttest design research. The population in this research were students of class XI IPA SMA N 1 Bojong in the academic year 2020/2021. The entire population was used as the research sample. Data collection methods used are test methods, interviews, questionnaires, and documentation. The data analysis technique used is the analysis prerequisite test including the normality and homogeneity tests. The final analysis or hypothesis testing in this research uses classical completeness test and t-test. The results showed that student learning independence in online physics learning assisted by problem based modules in terms of student cognitive learning outcomes has increased.